PERANCANGAN SISTEM KASIR PADA TOKO VINS CLEANING BERBASIS WEBSITE - Lughri Wijaya Pamungkas; Atainanur Hifdil Birri; Muhammad Rafli Valdrian; Ilham Albana (CV. Denasya Smart Publisher, 2026)
The development of information technology encourages business actors to utilize digital systems in managing business activities, including in the sales transaction process of services. Vins Cleaning Station Shop, which is engaged in the sale of shoe and bag washing services, still carries out a manual transaction recording process, which has the potential to cause errors in recording daily store summaries and difficulties in managing service data. This study aims to design and implement a website-based cashier system that can assist in the transaction process, summarizing the incoming and outgoing items being washed, and reporting systems every morning and evening effectively and efficiently. The methods used in this study include system analysis, system design, implementation, and system testing. The developed cashier system provides several main features including product data management, transaction recording, automatic payment calculations, and the presentation of summary reports every morning and evening. The results of this study indicate that this website-based cashier system is able to simplify the transaction process and management of service sales data at Vins Cleaning Station Shop. With this, the administrative process becomes more structured, faster, and more accurate, thereby increasing the operational efficiency of the store.